469 Soluble fiber in equine diets alters fecal characteristics. (7th December 2018) - Hansen, T; Cooney, L; Bobel, J; Rankins, E; Willemse, E; Adkin, A; Warren, L
Abstract: Sources of soluble fiber are often added to equine diets to increase overall digestible energy concentration while maintaining gut health. Almond hulls are a 1.6 million ton annual byproduct of the almond industry but have received little attention for use in equine diets. The objective of this study was to compare fecal characteristics from horses fed almond hulls to other common ingredients. We hypothesized the inclusion of soluble fiber from almond hulls or beet pulp would reduce fecal output. Four mature Quarter Horse geldings were fed 4 dietary treatments at 1.69% BW (DM basis) consisting of either 93% orchardgrass hay (ORCH), 53% orchardgrass hay and 40% molassed sugar beet pulp (MSBP), 53% orchardgrass hay and 40% almond hulls (HULL), or 59% orchardgrass hay and 34% crimped oats (OATS) in a 4 × 4 Latin square design. Each diet was supplemented with a vitamin-mineral pellet to meet requirements. After a 10-day dietary adaptation, a 3-day total fecal collection was performed. Data were analyzed as a Latin square design using a mixed model with significant means separated by Scheffe's method. Horses defecated more frequently ( P < 0.05) when fed ORCH (12.6 times/d) compared to other diets (8.8, SEM = 0.5). Individual defecation weight (as-excreted) was greater ( P < 0.05) for horses fed HULL (1.72 kg) compared to other diets (1.54, SEM = 0.08), but daily fecal output tended to be greatest ( P ≤ 0.1) for ORCH (18.4, SEM = 0.82 kg). Fecal DM ranged 23.0 to 27.3% (SEM = 0.7) and tended to differ ( P = 0.080) between dietary treatments. Soluble fiber sources reduced fecal output to similar levels of a mixed hay and grain diet. These data indicate digestibility and bulking capacity of different types of fiber alter fecal characteristics in horses.